Physiotherapy services required at primary health care level in Gauteng and Limpopo Provinces (Service provider's perspective physiotherapists/assistants) - Maleka, Morake Elias Douglas (My University, 2006)
ABSTRACT This study was conducted to determine the opinion of physiotherapists and physiotherapy assistants with regards to physiotherapy services required at a Primary Health Care (PHC) level in two provinces of South Africa, one being urban (Gauteng) and the other one more rural (Limpopo). Using a descriptive study design, a sample size consisting of 728 physiotherapists and assistants was selected from HPCSA register list. Data collection was by a self-administered questionnaire. Sixty six percent of physiotherapists in Gauteng Province and 68% in Limpopo Province agreed that promotive services are required whereas the percentage for physiotherapy assistants in Gauteng province and Limpopo province were 78% and 89% respectively. Preventative services were required by 82% and 85% by Physiotherapists and 95% and 96% by Physiotherapy assistants in Gauteng and Limpopo. 89% and 88% of Physiotherapists, 80% and 85% of Physiotherapy assistants in Gauteng and Limpopo respectively agreed that curative services are required. The rehabilitative services were required 83% and 90% by Physiotherapists, 85% and 95% by Physiotherapy assistants in Gauteng and Limpopo respectively. The provision of promotive, preventative, curative and rehabilitative services were seen as required in the two provinces in terms of physiotherapy services at a PHC level by both professional categories.
Masters report: Faculty of Health Sciences
Keywords: physiotherapy services; Primary Health Care; physiotherapists and physiotherapy